Implementasi Total Quality Management Berkaitan dengan Manajerial Perusahaan dan Keunggulan Bersaing (Implementation of Total Quality Management Related to Company Managerial and Competitive Advantage) - Gemina, Dwi; Silaningsih, Endang; Andari, Titiek Tjahya (Jurnal Aplikasi Manajemen, 2015)
Competitive advantageas TQM implementation measure, entrepreneur potential, business scale and business managementis constitutes company managerial. This research aims to determine the effects ofentrepreneur potential, business scale, business management on TQM, and TQM oncompetitive advantageat SMEs and Cooperatives in Bogor, Sukabumi. The research designs are verification; questionnaire distribution to 100 respondents. Research method is multiple regression. Data quality testing is validity test, reliability test, and classic assumption test. Hypothesis testing used simultaneous significant test, partial significant test. Research resullts show that first regression equation showed entrepreneur potential, business scale and business management at SMEs and Cooperatives in Bogor, Sukabumi simultaneously affected TQM. Business scaledid notpartially affect TQM at SMEs in Bogor, whereas entrepreneur potentialand business scaledid not partially affectSMEs in Sukabumi. Second regression equation showed TQM simultaneously affected competitive advantageat SMEs and Cooperatives in Bogor, Sukabumi. Partial effect showed focused on customers did not affect competitive advantage in Bogor, Sukabumi.